Low-intensity microwave irradiation does not substantially alter gene expression in late larval and adult Caenorhabditis elegans. - Dawe, Adam S.; Bodhicharla, Rakesh; Graham, Neil; May, Sean; Reader, Tom; Loader, Benjamin; Gregory, Andrew; Swicord, Mays; Bit-Babik, Giorgi; de Pomerai, David I. (Wiley, 2009)
Reports that low-intensity microwave radiation induces heat-shock reporter gene expression in the nematode, Caenorhabditis elegans, have recently been reinterpreted as a subtle thermal effect caused by slight heating. This study used a microwave exposure system (1.0 GHz, 0.5 W power input; SAR 0.9-3 mW kg-1 for 6-well plates) that minimises temperature differentials between sham and exposed conditions (≤0.1 °C). Parallel measurement and simulation studies of SAR distribution within this exposure system are presented. We compared 5 Affymetrix gene-arrays of pooled triplicate RNA populations from sham-exposed L4/adult worms against 5 gene-arrays of pooled RNA from microwave-exposed worms (taken from the same source population in each run). No genes showed consistent expression changes across all 5 comparisons, and all expression changes appeared modest after normalisation (≤ 40% up- or down-regulated). The number of statistically significant differences in gene expression (846) was less than the false-positive rate expected by chance (1131). We conclude that the pattern of gene expression in L4/adult C. elegans is substantially unaffected by low-intensity microwave radiation; the minor changes observed in this study could well be false positives. As a positive control, we compared RNA samples from N2 worms subjected to a mild heat-shock treatment (30ºC) against controls at 26 ºC (2 gene arrays per condition). As expected, heat-shock genes are strongly up-regulated at 30ºC, particularly an hsp-70 family member (C12C8.1) and hsp-16.2 . Under these heat-shock conditions, we confirmed that an hsp-16.2::GFP transgene was strongly up-regulated, whereas two non-heat-inducible transgenes (daf-16::GFP; cyp-34A9::GFP) showed little change in expression.